1990
DOI: 10.1111/j.1439-0450.1990.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Violet Mink Develop an Acute Disease after Experimental Infection with Aleutian Disease Virus (ADV) Isolate ADV SL3

Abstract: Summary Six‐Aleutian (aa)‐genotype violet mink were infected intraperitoneally with the Aleutian Disease Virus (ADV) bone marrow derived isolate ADV SL3. All animals developed virus‐specific antibodies and hypergammaglobulinaemia. Mortality during the fourteen week duration of the infection was 50%. The virus induced (histo)pathological lesions typical for Aleutian Disease. By immunohistochemical examination using a virus capsid‐specific monoclonal antibody viral antigen was detected in lymph nodes, spleen, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The results of our study reveal a distinct extranuclear localization of viral antigen and fail to demonstrate the nuclear presence of A D viral proteins generally accepted as evidence of ADV replication in vitro (VAN DAWEN et al, 1983). This confirms findings obtained in previous immunohistological and in situ-hybridization studies performed on lymphoid tissues from experimentally infected mink indicating a viral sequestration in this particular location of lymphoid follicles (ALEXANDERSEN et al, 1988;HAAS et al, 1990). It is unlikely that follicular dendritic cells are major target cells, because their intrinsic mitotic rate, even in immunized animals is very low (TEW et al, 1982) and as known from other parvoviruses an active D N A metabolism is a requirement for parvoviral replication (COTMORE and TATTERSALL, 1987).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of our study reveal a distinct extranuclear localization of viral antigen and fail to demonstrate the nuclear presence of A D viral proteins generally accepted as evidence of ADV replication in vitro (VAN DAWEN et al, 1983). This confirms findings obtained in previous immunohistological and in situ-hybridization studies performed on lymphoid tissues from experimentally infected mink indicating a viral sequestration in this particular location of lymphoid follicles (ALEXANDERSEN et al, 1988;HAAS et al, 1990). It is unlikely that follicular dendritic cells are major target cells, because their intrinsic mitotic rate, even in immunized animals is very low (TEW et al, 1982) and as known from other parvoviruses an active D N A metabolism is a requirement for parvoviral replication (COTMORE and TATTERSALL, 1987).…”
Section: Discussionsupporting
confidence: 88%
“…According to previous immunohistological findings (PORTER et al, 1969;RACE et al, 1986;HAAS et al, 1990) viral antigen was found in the cytoplasm of Kupffer cells. A prerequisite for the demonstration of viral proteins was to perform an elution procedure on cryosections.…”
Section: Discussionmentioning
confidence: 66%
“…The target cells of ADV in vivo are lymphoid cells, most likely of the B-cell lineage (KAADEN et al, 1986;HAAS et al, 1990) and cells of the macrophage lineage (KANNO et al, 1992). By strand-specific in situ hybridization viral replication could be demonstrated in lymph nodes, spleen, peripheral blood lymphocytes and bone marrow cells of infected mink (ALEXANDERSEN et al, 1988;HAAS et al, 1990 Thus a block during viral DNA replication or transcription in (certain) lymphoid target cells (bone marrow) might lead to an inefficient nicking of the Mccl RF DNA. This could result in a restricted infection with low-level virion synthesis, and the resulting permanent antigenic stimulus may be one mechanism contributing to the Aleutian disease virus persistence in wiwo.…”
Section: The MCCL Rf D N a Is An Intermediate Of Aleutian Disease Parmentioning
confidence: 99%
“…However, the specific virus strain as well as the age and genotype of the mink strongly influence whether this classical picture occurs after infection (23,40,42,43).…”
mentioning
confidence: 99%